THE EFFECTIVENESS OF DIFFERENTIAL CLASSROOM MANAGEMENT ON THE PSYCHOLOGICAL WELL-BEING OF STUDENTS WITH DISABILITIES - Abidin, Zaenal (Medical Journal of Nusantara, 2025)
This study aims to analyze the effectiveness of differentiated classroom management in improving the psychological well-being of students with intellectual disabilities at SLB Ungaran Barat. The research employed a quasi-experimental approach using a non-equivalent control group design. The participants consisted of an experimental group receiving differentiated classroom management treatment and a control group receiving conventional classroom management. Data were collected through a psychological well-being scale, structured observations, and teacher interviews. The indicators of psychological well-being included self-confidence, emotional stability, social participation, and learning motivation. The findings revealed a significant increase in the psychological well-being scores of the experimental group compared to the control group, with a large effect size. These results indicate that the implementation of differentiated classroom strategies positively contributes to improving mental health and socio-emotional development among students with intellectual disabilities. The study recommends differentiated classroom management as a sustainable pedagogical strategy in special education to support students’ holistic development.